ZAKAT DISTRIBUTION MANAGEMENT OF NATIONAL AMIL ZAKAT AGENCY OF WEST KALIMANTAN PROVINCE - RAZIKI WALDAN (Jurnal Al-Hikmah: Jurnal Dakwah, 2020)
The potential of zakat is quite significant in National Amil Zakat Agency (BAZNAS) West Kalimantan Province. In addition to the obligation to distribute, the BAZNAS West Kalimantan Province is also expected to make efforts to empower mustahiq so that the purpose of zakat to improve people's lives is achieved. The research question posed is: How is the zakat distribution management of the BAZNAS of the West Kalimantan Province? The method used in this research is a descriptive method with a qualitative approach. Data sources in this study are the management and staff of the BAZNAS of West Kalimantan Province and the recipients of zakat recipients. The data collection techniques used are observation, in-depth interviews, and documentation. Data analysis used is data collection, data reduction, data display (display data), and concluding (verification). The final step taken is checking the validity of the data using the triangulation of data, member checking, and adequacy of references. In general, the results of this study concluded that the implementation of the empowerment of mustahiq zakat at the BAZNAS of West Kalimantan province had gone well according to management theory, although there were a few shortcomings. Potensi zakat cukup signifikan pada Badan Amil Zakat Nasional (BAZNAS) Provinsi Kalimantan Barat. Selain kewajiban mendistribusikan, BAZNAS Provinsi Kalimantan Barat juga diharapkan melakukan upaya pemberdayaan mustahiq, sehingga tujuan zakat untuk meningkatkan kehidupan masyarakat dapat tercapai. Pertanyaan penelitian yang diajukan adalah: Bagaimana manajemen distribusi zakat BAZNAS Provinsi Kalimantan Barat? Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan pendekatan kualitatif. Sumber data dalam penelitian ini adalah manajemen dan staf BAZNAS Provinsi Kalimantan Barat dan penerima penerima zakat. Teknik pengumpulan data yang digunakan adalah observasi, wawancara mendalam, dan dokumentasi. Analisis data yang digunakan adalah pengumpulan data, reduksi data, tampilan data (display data), dan penarikan kesimpulan (verifikasi). Langkah terakhir yang diambil adalah memeriksa validitas data menggunakan triangulasi data, pengecekan anggota, dan kecukupan referensi. Secara umum, hasil penelitian ini menyimpulkan bahwa pelaksanaan pemberdayaan zakat mustahiq di BAZNAS provinsi Kalimantan Barat telah berjalan dengan baik menurut teori manajemen, meskipun ada beberapa kekurangan.